Recurrent, Delayed Hemorrhage Associated with Edoxaban after Deep Brain Stimulation Lead Placement. (13th January 2013) - Sivakumar, Walavan; Garber, Sarah T.; Schrock, Lauren E.; House, Paul A.
Abstract : Factor-Xa inhibitors like edoxaban have been shown to have comparable or superior rates of stroke and systemic embolization prevention to warfarin while exhibiting lower clinically significant bleeding rates. The authors report a case of a man who presented with delayed, recurrent intracranial hemorrhage months after successful deep brain stimulator placement for Parkinson disease while on edoxaban for atrial fibrillation. Further reports on the use of novel anticoagulants after intracranial surgery are acutely needed to help assess the true relative risk they pose.